Transparent, Pliable, Antimicrobial Hydrogels for Ocular Wound Dressings - Tao Liu; Eleonore C.L. Bolle; Traian V. Chirila; Marion Buck; Daniel Jonas; Shuko Suzuki; Tai Smith; V. Prasad Shastri; Tim R. Dargaville; Aurelien Forget (Applied Sciences, 2020)
Following ocular surgery, dressings are commonly applied to the surgical wound. These dressings need to combine medical properties with ease of use while maintaining comfort for the patient. For the ocular area, this means that the dressings need to act as a microbial barrier, allow good conformability to the contours of the eye, and provide evaporative cooling to the inflamed area. Furthermore, the dressings should be transparent to allow for the inspection of the wound site by healthcare professionals without the need for removal. In this paper, we investigate a blend of native agarose (NA) and carboxylated agarose (CA) for producing elastic hydrogels with high water content that can be supplemented with antibiotics. It was found that in comparison to pure agarose hydrogels, the NA hydrogels blended with CA had a reduced Young’s modulus, reduced evaporation rate when exposed to air, and accelerated release rate of antimicrobial agents, whilst maintaining the same degree of transparency. By altering the formulation from 2 wt.% pure NA to 1 wt.% NA blended with 1 wt.% CA, we were able to observe an approximately 55% reduction in Young’s modulus, 25% reduction in evaporation rate, as well as a significant acceleration in the release rate of cefazolin and doxycycline, making this hydrogel blend a potential material for topical treatment applications.